Bottom-up supramolecular assembly in two dimensions. Issue 11 (10th February 2022) - Insua, Ignacio; Bergueiro, Julian; Méndez-Ardoy, Alejandro; Lostalé-Seijo, Irene; Montenegro, Javier
Abstract : The self-assembly of molecules in two dimensions (2D) is gathering attention from all disciplines across the chemical sciences. This perspective discusses the main strategies to direct the supramolecular self-assembly of organic monomers in 2D. Abstract : The self-assembly of molecules in two dimensions (2D) is gathering attention from all disciplines across the chemical sciences. Attracted by the interesting properties of two-dimensional inorganic analogues, monomers of different chemical natures are being explored for the assembly of dynamic 2D systems. Although many important discoveries have been already achieved, great challenges are still to be addressed in this field. Hierarchical multicomponent assembly, directional non-covalent growth and internal structural control are a just a few of the examples that will be discussed in this perspective about the exciting present and the bright future of two-dimensional supramolecular assemblies.